Intestinal dysbiosis and allogeneic hematopoietic progenitor cell transplantation. Issue 1 (December 2016) - Raghunathan, Vikram; Sheng, Iris; Lim, Seah
Abstract The intestinal microbiota is a diverse and dynamic ecosystem that is increasingly understood to play a vital role in human health. Hematopoietic stem cell transplant recipients undergo prolonged exposure to antimicrobials, chemotherapeutic agents, and immunosuppressants, resulting in profound shifts in the gut microbiome. A growing body of research has revealed the ways in which these microbiologic shifts shape immune modulation, affecting susceptibility to infections and graft-versus-host disease, the two major post-transplant complications in this population. As transplant medicine becomes increasingly personalized, the potential for microbiome-modulating treatments holds immense potential. Strategies to preserve the intestinal microbiota, including targeted antibiotics, prebiotics and probiotics, and fecal microbiota transplant could mitigate some of the microbiologic shifts in stem cell transplant recipients, and reduce the incidence of peri-transplant morbidity and mortality.